Extraction, Quantification and Characterization Techniques for Anthocyanin Compounds in Various Food Matrices—A Review - Oana Emilia Constantin; Daniela Ionela Istrati (Horticulturae, 2022)
Anthocyanins are water-soluble pigments characterized by various intense colors found in fruits and vegetables. Scientific studies have shown growing evidence to support their health benefits. Therefore, estimating the anthocyanin content in food is essential to identify the ideal analytical method. Moreover, due to the instability of plant anthocyanins, it is important to select and optimize their extraction, separation and qualitative and quantitative analysis, steps that are indispensable and important in their study. The present article reviews the latest procedures for extracting anthocyanins from various food matrices and analytical methods for their quantification. Therefore, various forms of preliminary treatments of samples for anthocyanin extraction, extraction procedures for various fruits, vegetables and cereals, purification of samples and quantification of anthocyanins are highlighted and evaluated. Using ultrasound-assisted extraction (UAE) might be effective for anthocyanin extraction and the Amberlite XAD-7HP method is the most effective for purifying anthocyanins. Combining the liquid chromatography (LC) method with electrospray ionization (ESI) and mass spectrometry (MS) or quadrupole time-of-flight (QTOF) with mass spectrometry (MS) better quantifies the anthocyanins in the food complex samples. Therefore, the extraction and separation of anthocyanins and their qualitative and quantitative analyses are essential steps in their research. As a result, the study concentrates on a detailed characterization of various qualitative and quantitative analytical methodologies, while briefly describing the main anthocyanin extraction processes.